2023
DOI: 10.1186/s13019-023-02104-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on the outcomes of minimally invasive direct coronary artery bypass

Abstract: Background Tobacco smoking has been associated with an increased risk of complications after conventional coronary surgery. However, the impact of smoking on the risk of postoperative complications in minimally invasive coronary surgery is yet to be studied. We aimed to analyze the impact of the preoperative smoking status on the short- and long-term outcomes of minimally invasive direct coronary artery bypass grafting (MIDCAB) in the context of isolated surgical revascularization or in associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…To a certain extent, the use of high-dose sufentanil can avoid irreversible myocardial injury and necrosis, improve myocardial energy supply, and maintain electrophysiological stability before the opening of the ascending aorta, which is beneficial to the recovery of cardiac function and smooth heart rebound of patients. In addition, similar to previous studies, [33][34][35] this study confirmed that the history of preoperative smoking and atrial fibrillation were significantly associated with spontaneous heart rebound during CPB. However, multivariate logistics regression analysis did not show a correlation between spontaneous rebound success and other known risk factors, which may be due to the small sample size of this study, or because the medical data of patients undergoing cardiac surgery under CPB were collected and analyzed in only one tertiary medical center.…”
supporting
confidence: 91%
“…To a certain extent, the use of high-dose sufentanil can avoid irreversible myocardial injury and necrosis, improve myocardial energy supply, and maintain electrophysiological stability before the opening of the ascending aorta, which is beneficial to the recovery of cardiac function and smooth heart rebound of patients. In addition, similar to previous studies, [33][34][35] this study confirmed that the history of preoperative smoking and atrial fibrillation were significantly associated with spontaneous heart rebound during CPB. However, multivariate logistics regression analysis did not show a correlation between spontaneous rebound success and other known risk factors, which may be due to the small sample size of this study, or because the medical data of patients undergoing cardiac surgery under CPB were collected and analyzed in only one tertiary medical center.…”
supporting
confidence: 91%